Monitoring Pathogen‐Induced Sickness in Mice and Rats. Issue 2 (19th June 2017) - Kolmogorova, Daria; Murray, Emma; Ismail, Nafissa
Abstract : Sickness behavior monitoring, a technique for examining the development of sickness symptomatology following infection, is necessary in experiments studying neurochemical and physiological changes associated with pathogen‐induced immune activation. However, the results of sickness behavior monitoring are difficult to reconcile due to inconsistencies in protocol methods and rater bias. The protocol described herein offers a non‐invasive and unbiased approach to assess the progression of pathogen‐induced sickness behaviors. This simple, straightforward method uses a five‐point scale to assess animals for the presence of four sickness behaviors (i.e., '"0" = no sickness behaviors; "4" = four sickness behaviors) at various time points following exposure to a pathogen. This approach removes the ambiguity and bias inherent to other methods of sickness behavior monitoring that rely on subjective ratings of severity for individual symptoms. This protocol has been successfully applied to male and female rodents injected intraperitoneally with lipopolysaccharide and polyinosinic:polycytidylic acid, and has been effective in pubertal and adult populations. Protocols for changes in body temperature and weight are also provided as physiological markers of sickness. © 2017 by John Wiley & Sons, Inc.